Evaluating the effects of land use and strategies for parking and transit supply on mode choice of downtown commuters - Seyed Amir H Zahabi; Luis. F. Miranda-Moreno; Zachary Patterson; Philippe Barla (Journal of Transport and Land Use)
Metropolitan regions around the world are looking for sustainable strategies to battle energy consumption and emissions. These strategies include land use policies and the desire to decrease the externalities from transportation and therefore increase the share of public transit use. The goal of this research is to better understand the relationships between Land-use (LU), public transit accessibility (PT), parking policies, and mode choice for suburban Montreal commuters. In this regard we evaluate the potential impact of land-use, transit accessibility and parking policies on the mode choice of the households dwelling in commuter rail line catchments in the region of Montreal, Canada. The approach adopted here is to consider mode choice as a joint decision with neighborhood type choice, based on neighborhood typologies derived using a cluster analysis characterized by land use variables. Also, the effect of parking fees on mode choice is investigated and quantified. The method used in this study is a simultaneous modeling approach to account for the endogeneity of mode and household location choice. The model system is made up of two models – a neighborhood type choice model and a mode choice model. The results demonstrate the robustness of the models and methodology implemented thus providing important innovations for transportation and land-use planning.